Bentuk Wacana dalam Debat Pilpres 2024: Kajian Wacana - Islam, M. Zarkawi; Setiyadi, DB Putut; Abidin, Lalu Abd Muhyi; Hersulastuti, Hersulastuti; Haryono, Purwo (Indo-MathEdu Intellectuals Journal, 2025)
The general aim of this study is to enhance students' understanding of communication strategies in public spaces, particularly in the context of the presidential election debates. This research adopts a qualitative approach using critical discourse analysis methods to explore the phenomenon of the 2024 presidential election debates. The research data is collected from primary sources in the form of video recordings from YouTube, as well as secondary sources such as books and articles. The data collection techniques are conducted through observation, in-depth interviews, and documentation. The research results show that the discourse built in the 2024 presidential election debate includes a variety of important themes, such as education, health, transportation, economy, diversity, and social inclusion. Each of these themes is expressed in a varied and strategic manner by the candidates to attract sympathy and attention from voters. This research also identifies that the delivery of arguments involves various styles of language, including a persuasive style that focuses on stirring the emotions of the audience, a pragmatic style that offers concrete solutions, and a millennial style that uses familiar language that is easy for the younger generation to understand. The analysis of macro structural elements shows that all these discourses are interconnected and have a strong relevance to the role of the presidential candidate as the leader of the nation. Meanwhile, the analysis of micro structural elements reveals the use of language rich in meaning, as well as rhetorical techniques designed to strengthen the appeal of the arguments.